METODE CASE BASED REASONIG (CBR) PADA SISTEM DIAGNOSA PENYAKIT KULIT - -, Fitria; Lestari, Sri; Diantoro, Wawan (Jurnal Informatika, 2018)
Health is a very important thing since it affects daily activities. If we have health disturbance, we certainly do not like it. One of these disturbances is skin disease. When we want to identify skin disease we usually visit a doctor. However, we sometimes find a problem in handling this skin disease identification which may be influenced by the high cost of visiting doctor. Because of this reason, an expert application system is needed as consultation assistance to replace doctorâs role in giving solution toward problems related to skin disease.This study uses Case-Based Reasoning (CBR) method, of which CBR is one of knowledge based approach methods to study and solve problems according to problem experience in the past to be stored in a system called case-based. In this case, there are 44 different symptoms and 14 kinds of skin diseases. The management of data similarity uses attributive value with the closest margin. These values are calculated by using Nearest Neighbor method in order to find out the highest similarity value among existing 14 old cases. In accordance with the input result from the existing case example it shows that the result of manual calculation and system calculation are the same. This system can assist in diagnosing kinds of skin disease by taking conclusion obtained from the highest similarity value from the existing cases based on some symptoms which are input by the users (patient), and the system can also give solution in handling the problems.Â Keyword: Skin Disease, CBR, Nearest Neighbor